2007
DOI: 10.1099/jmm.0.46817-0
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and antifungal susceptibility of Candida bloodstream isolates in Kuwait: a 10-year study

Abstract: Bloodstream infections due to Candida species are important complications in severely ill hospitalized patients. This study presents data on species distribution and antifungal susceptibility profiles of Candida bloodstream isolates obtained from Kuwait during a 10-year period. All the bloodstream isolates were identified to species level by the germ tube test and carbohydrate assimilation profile using the VITEK 2 yeast identification system. Using E-test strips for amphotericin B, fluconazole, 5-flucytosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
60
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 31 publications
31
60
1
9
Order By: Relevance
“…Currently, other species of this genus have been found to cause an increasing number of cases of candidiasis (Mokaddas et al, 2007;Pereira et al, 2010;Das et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, other species of this genus have been found to cause an increasing number of cases of candidiasis (Mokaddas et al, 2007;Pereira et al, 2010;Das et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As PCR is expensive and not available at all places, it was observed in the present study that species identification of Candida can be done by using Hichrome agar (Mokaddas et al, 2007) and the isolates were further confirmed by sugar assimilation and other biochemical tests. This indicates that Hichrome agar can be used at field level for rapid presumptive identification.…”
Section: Resultsmentioning
confidence: 87%
“…VOR resistance has been reported to emerge recently under VOR treatment from 0.3-10 % in different studies. Since frequent use of VOR was reported to be related to both probable and possible Aspergillus infections [35][36][37]. Either L-AmB or CAS is recommended for the treatment of fungemia caused by azole-resitant Candida species.…”
Section: Discussionmentioning
confidence: 99%